Legitimacy of the courts: evidence from a survey in Punjab, Pakistan - Asif, Muhammad (International journal of comparative and applied criminal justice, 2025)
Procedural justice is generally considered a primary indicator by which legal authorities, such as police and courts, establish legitimacy. However, considering the context of the criminal justice system in Pakistan, this paper examines whether the perceptions of accurate verdicts, along with perceptions of procedural justice, are associated with the perceptions of legitimacy of the courts. The data for this cross-sectional study come from an online survey of the general population in Punjab, Pakistan. The results of the multiple regression models affirm the study hypotheses. The findings suggest that people are judgemental; they not only evaluate whether the authorities (judges) act procedurally in just ways during encounters with the public but also retrospectively keep a record of previous memories regarding court verdicts. These memories shape their perceptions of whether the authorities are legitimate.